Associations among imaging measures (2): The association between gray matter concentration and task‐induced activation changes. Issue 1 (11th September 2012) - Takeuchi, Hikaru; Taki, Yasuyuki; Nouchi, Rui; Hashizume, Hiroshi; Sassa, Yuko; Sekuguchi, Atsushi; Kotozaki, Yuka; Nakagawa, Seishu; Nagase, Tomomi; Miyauchi, Carlos Makoto; Kawashima, Ryuta
<x xml:space="preserve">Abstract</x> The association between functional activation and gray matter (GM) structure has been revealed in clinical studies and studies of aging involving a small number of subjects. The purpose of this study was to investigate the association between functional activation maps and GM structures in young adults who do not show apparent GM atrophy and to investigate in detail the nature of this association using a large number of subjects. We used voxel‐by‐voxel regression analyses to investigate voxel‐by‐voxel associations between GM concentration (GMC) and contrast estimate images of brain activity during n‐back working memory tasks. Associations were assessed for each voxel after regressing out the effects of age, sex, and mean signal intensity during functional magnetic resonance imaging scanning at each voxel using data from 248 normal, right‐handed, young adult subjects. In our study, the concept of "the greater the GMC, the greater the task‐related activation increase/task‐related activation decrease (or the greater the task‐related activation change from baseline)" was true for a wide range of activated and deactivated areas. However, in some minor regions, the other pattern of "the greater the GMC, the smaller the task‐related activation increase" was observed. The first pattern is often observed at the borders of GM structures. These findings may have to be taken into consideration when group/individual differences in functional activation are investigated. Hum Brain Mapp 35:185–198, 2014. © 2012 Wiley Periodicals, Inc.